Tinnitus reduction in patients with single-sided deafness: the effect of cochlear implantation, bone conduction devices, and contralateral routing of sound hearing aids investigated in a randomized controlled trial - Wendrich, Anne W.; Assouly, Kelly K. S.; van Heteren, Jan A. A.; Peters, Jeroen P. M.; Grolman, Wilko; Stokroos, Robert J.; Versnel, Huib; Smit, Adriana L. (Frontiers in Neurology, 2024)
Single-sided deafness (SSD) is often accompanieds by tinnitus, resulting in decreased quality of life. Currently, there is lack of high level of evidence studies comparing different treatment options for SSD with regard to tinnitus reduction. This randomized controlled trial (RCT) evaluated the effect of a cochleair implant (CI), bone conduction device (BCD), contralateral routing of sound (CROS) and no treatment on tinnitus outcomes in SSD patients, up to 24 months of follow-up. 120 adult SSD patients were randomized to 3 groups: CI, a trial period with first a BCD on a headband, then a CROS, or vice versa. After the trial periods, patients opted a BCD, CROS, or no treatment. At the start of follow-up, 28 patients were implanted with a CI, 25 with a BCD, 34 had a CROS, and 26 chose no treatment. The Tinnitus Handicap Inventory (THI), Tinnitus Questionnaire (TQ), Visual Analogue Scale (VAS) and the Hospital Anxiety and Depression Scale (HADS) were completed at baseline, and at 3, 6, 12, and 24 months of follow-up. The CI and BCD groups showed significantly decreased tinnitus impact scores. The CI group showed the largest decrease, which was already observed at 3 months of follow up. Compared to baseline, the median THI score decreased with 23 points, the TQ score with 17 points and the VAS score with 60 points at 24 months. In the BCD group, the TQ score decreased with 9 points and the VAS decreased with 25 points at 24 months. The HADS anxiety subscale showed no indication for anxiety at baseline for all groups. The depression subscale showed scores indicating possible depression for all groups at baseline, these scores only significantly decreased in the CI group at 24 months.In this RCT, SSD patients treated with a CI or BCD showed overall decrease on tinnitus impact scores up to 24 months compared to baseline. The CI-group reported a stable and the largest reduction. Cochlear implants appear to be superior to BCD, CROS and no treatment in achieving partial or complete resolution of tinnitus in patients with SSD.